Enhancing Sulfur Tolerance of Ni-Based Cermet Anodes of Solid Oxide Fuel Cells by Ytterbium-Doped Barium Cerate Infiltration - Li, Meng; Hua, B.; Luo, J.; Jiang, S.; Pu, J.; Chi, B.; Li, J. (American Chemical Society, 2016)
Conventional anode materials for solid oxide fuel cells (SOFCs) are Ni-based cermets, which are highly susceptible to deactivation by contaminants in hydrocarbon fuels. Hydrogen sulfide is one of the commonly existed contaminants in readily available natural gas and gasification product gases of pyrolysis of biomasses. Development of sulfur tolerant anode materials is thus one of the critical challenges for commercial viability and practical application of SOFC technologies. Here we report a viable approach to enhance substantially the sulfur poisoning resistance of a Ni-gadolinia-doped ceria (Ni-GDC) anode through impregnation of proton conducting perovskite BaCe0.9Yb0.1O3-d (BCYb). The impregnation of BCYb nanoparticles improves the electrochemical performance of the Ni-GDC anode in both H2 and H2S containing fuels. Moreover, more importantly, the enhanced stability is observed in 500 ppm of H2S/H2. The SEM and XPS analysis indicate that the infiltrated BCYb fine particles inhibit the adsorption of sulfur and facilitate sulfur removal from active sites, thus preventing the detrimental interaction between sulfur and Ni-GDC and the formation of cerium sulfide. The preliminary results of the cell with the BCYb+Ni-GDC anode in methane fuel containing 5000 ppm of H2S show the promising potential of the BCYb infiltration approach in the development of highly active and stable Ni-GDC-based anodes fed with hydrocarbon fuels containing a high concentration of sulfur compounds.